2002
DOI: 10.1046/j.1469-0705.2002.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamics and fetal behavioral states

Abstract: The results of this study provide evidence of the influence of different fetal behavioral states on fetal cerebral hemodynamic patterns. We believe it is better to sample the proximal segment in clinical practice because it is less influenced by fetal behavioral state. This information should be considered when evaluating fetal cerebral hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
(17 reference statements)
4
19
0
Order By: Relevance
“…Measurements from the middle and distal thirds have significantly higher indices than those from the proximal third., 4 but the proximal third appears to be less variable during changes in fetal behavioral state. 5 The sensitivity of the CPR from our study is similar to those previously reported for predicting adverse perinatal outcomes in IUGR. 2 In conclusion, CPR should be used in prenatal monitoring of pregnancies with suspected SGA.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Measurements from the middle and distal thirds have significantly higher indices than those from the proximal third., 4 but the proximal third appears to be less variable during changes in fetal behavioral state. 5 The sensitivity of the CPR from our study is similar to those previously reported for predicting adverse perinatal outcomes in IUGR. 2 In conclusion, CPR should be used in prenatal monitoring of pregnancies with suspected SGA.…”
Section: Discussionsupporting
confidence: 77%
“…The flow velocity waveforms were recorded from umbilical artery (UA) and fetal middle cerebral artery (MCA) at proximal third. 4,5 PI of UA and fetal MCA were recorded and ratio of MCA PI to UA PI (Cerebroplacental Doppler ratio) was calculated. The pregnancies were followed-up and the final perinatal outcome of each case was noted.…”
Section: Methodsmentioning
confidence: 99%
“…When examining the middle cerebral artery, the sampling site has significant effects on the Doppler measurements when the PI is used. Measurements from the middle and distal thirds have significantly higher indices than those from the proximal third8 but the proximal third appears to be less variable during changes in fetal behavioral state13. The clinical relevance of Doppler ratios constructed from different sites has not been evaluated to date.…”
Section: Discussionmentioning
confidence: 99%
“…The average of fetus heart pulse rate during the immovability was remarkably lower than the motion phase (p= 0.0047). However, there was no significant relation between PI of the proximal and distal parts of MCA in different behavior conditions of the fetus (22). Abel DE.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, there was a remarkable relation between umbilical artery PO2, PI of proximal and distal parts of MCA (positive), and occurrence of elective Cesarean section (negative) (24). Clerici, who has worked in this field, could not find a sharp relation between PI and pulse rate of the fetus (22). We believe that although the present study presents valuable information, there is need to perform similar studies in other races and geographical areas, as well as patients with a history of metabolic and or vascular diseases, in order to find a better concept regarding the vascular changes in fetus.…”
Section: Discussionmentioning
confidence: 99%